Dari nilai ke aksi: Menjadikan pancasila sebagai gerakan anti korupsi milenial - alfaruq, m.fathuz zahir (Maliki Interdisciplinary Journal, 2025)
This article explains how Pancasila can serve as a moral and social foundation for building an anti-corruption movement in Indonesia, particularly for the millennial generation. As the foundation of the state, Pancasila embodies fundamental values ​​such as honesty, social justice, responsibility, and belief in God, which serve as guidelines for the nation's life. These values, if consistently implemented, can strengthen the nation's character, embodying integrity and ethics. The research was conducted using a descriptive, literature-based qualitative method that reviewed various scientific sources related to Pancasila values ​​and efforts to eradicate corruption. The results show that internalizing Pancasila values ​​in education and social life can foster strong anti-corruption awareness. Furthermore, millennials play a crucial role as agents of change, spreading the anti-corruption spirit through social media and digital technology. However, the implementation of Pancasila values ​​in the anti-corruption movement faces obstacles such as weak law enforcement, a permissive culture of corruption, and the influence of a materialistic lifestyle. Nevertheless, technological developments and the active participation of the younger generation present significant opportunities to build a culture of integrity and transparency in society.